Analysis of the Influence of Development of Builded Land on the Increase of Surface Temperature Related to the Urban Heat Island Phenomenon in Depok City - Bayu Aditya Pratama; Jumadi (Amcolabora, 2022)
Depok City is a satellite city with a strategic location, thus triggering urbanization. Urbanization is one of the causes of the increase in population, in 2011 the population of Depok City reached 1,813,612 people, in 2021 it would become 2,056,335 people. The increase in population and limited urban land resulted in the conversion of non-built land use into built-up land. Built-up land absorbs and reflects heat, so the surface temperature is high. The development of built-up land can result in an increase in surface temperature and trigger the Urban Heat Island (UHI) phenomenon. This study aims to identify the distribution of land cover and surface temperature, analyze the ef ect of built-up land cover development on the increase in surface temperature, and analyze the relationship between the increase in surface temperature and the distribution of UHI in Depok City in 2011 and 2021. Landsat image data processing methods are used to obtain classifications. land cover using the Maximum Likelihood algorithm, a survey was conducted to validate the results, then the classification of surface temperature was obtained using the Mono-Window Brightness Temperature algorithm. UHI identification is obtained by using the threshold value equation. The ef ect of built-up land cover development on the increase in surface temperature was tested using simple linear regression. The results showed the development of the distribution of built-up land cover, in 2011 it had an area of 116.98 Km2 to 150.87 Km2 in 2021. The distribution of surface temperatures in Depok City in 2011 was dominated by class II surface temperatures with an area of 132.29 Km2, while in 2021 dominated by surface temperature class IV with an area of 126.03 Km2. The development of built-up land cover has an influence on the increase in surface temperature by 40.5%. The increase in surface temperature is directly proportional to the increase in the UHI threshold value, the distribution of UHI in Depok City in 2011 has an area of 52.09 Km2 to 65.63 Km2 2 in 2021.